Erasmus University Rotterdam wrestles with sustainability strategy - Wijen, Frank; Coughlan, Geraldine; Yue, Tao, 1976- (London : Rotterdam School of Management, Erasmus University, 2013)
Erasmus University Rotterdam (EUR) is in the midst of a sustainability dilemma. The university is in a stage of transition, shifting focus from the city to the world stage. EUR's current environmental sustainability policy needs more impetus. The university wants to incorporate sustainability into its new strategy (2013-2018) to become more competitive. But with reduced government funding, EUR has fewer resources to promote sustainability. The crux of EUR's dilemma is how more than 20,000 EUR students and 2,500 employees can be sensitised to, and induced to act upon, sustainability - even though it is not necessarily a priority for them. EUR is a university with a strong business, economics, law and medicine focus - therefore, the students' primary goal is traditionally a good career first. The crucial question is thus how to win a place in the students' and employees' hearts and minds for sustainability in the broader sense.
Originally published in Wijen, F. & Coughlan, G. (2013). Erasmus University Rotterdam wrestles with sustainability strategy. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Erasmus Universiteit Rotterdam -- Case studies; Universities and colleges -- Netherlands -- Rotterdam -- Administration -- Case studies; Sustainability -- Case studies